2023
DOI: 10.3390/cancers15041168
|View full text |Cite
|
Sign up to set email alerts
|

CTTN Overexpression Confers Cancer Stem Cell-like Properties and Trastuzumab Resistance via DKK-1/WNT Signaling in HER2 Positive Breast Cancer

Abstract: Background: Despite the therapeutic success of trastuzumab, HER2 positive (HER2+) breast cancer patients continue to face significant difficulties due to innate or acquired drug resistance. In this study we explored the potential role of CTTN in inducing trastuzumab resistance of HER2+ breast cancers. Methods: Genetic changes of CTTN and survival of HER2+ breast cancer patients were analyzed in multiple breast cancer patient cohorts (METABRIC, TCGA, Kaplan-Meier (KM) plotter, and Hanyang University cohort). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The absence of any association between cortactin expression and the prognosis of patients with breast cancer in these two studies is probably explained by the fact that the molecular subtypes of breast cancer were not separately analyzed in these studies. This assumption is supported by a recent study where cortactin overexpression in a HER2-type breast cancer was found to be associated with poor clinical outcome like other carcinomas [27]. Unlike the HER2-type breast cancer, cortactin protein expression in TNBC breast cancer is associated with good prognosis based on our data.…”
Section: Discussionsupporting
confidence: 91%
“…The absence of any association between cortactin expression and the prognosis of patients with breast cancer in these two studies is probably explained by the fact that the molecular subtypes of breast cancer were not separately analyzed in these studies. This assumption is supported by a recent study where cortactin overexpression in a HER2-type breast cancer was found to be associated with poor clinical outcome like other carcinomas [27]. Unlike the HER2-type breast cancer, cortactin protein expression in TNBC breast cancer is associated with good prognosis based on our data.…”
Section: Discussionsupporting
confidence: 91%
“…These results are promising as no validated biomarker, apart from HER2, can predict the benefit of the Tz approach, and thus guide individual therapeutic decisions [24]. Other authors have established a relation between cortactin and vinculin overexpression and cancer aggression and resistance, and have also proposed them as promising prognostic and predictive biomarkers [71][72][73]. These proteins could be related as a study linked them, wherein vinculin mediated the action of cortactin [74].…”
Section: Discussionmentioning
confidence: 99%
“…The canonical Wnt protein activates transcription of β-catenin/T-cell factor (TCF)/lymphatic enhancing factor (LEF) target genes by transducing signaling β-catenin ( 23 , 24 ). Some researchers have demonstrated that Wnt antagonists with frequent genetic and epigenetic mutations in breast cancer led to β-catenin-mediated activation of Wnt target genes, suggesting that the Wnt-catenin-β1 (CTNNB1) signaling pathway plays an important role in the oncogenic process ( 25 , 26 ). Similarly, it has been reported in breast cancer that several cytosolic and nucleus components of the Wnt/β-catenin pathway is deregulated, such as DKK3, Dickkopf (DKK)-1, APC, Wnt inhibitor factor 1 (WIF1), SFRP5, MCC, glycogen synthase kinase-3β (GSK3B), and CTNNBIP1 ( 27 - 29 ).…”
Section: Introductionmentioning
confidence: 99%